The Function of Wayang Kulit in the Spreading of Islamic Religy in Demak at 16th Century - Anang Ari Indriyanto; Sumarno Sumarno; Kayan Swastika (History Education, University of Jember, 2018)
This study aims to measure the function of wayang kulit before the 16th century, meaning the function of wayang kulit in the spread of Islam in Demak in the 16th century and the introduction of wayang kulit as a medium for the spread of Islam to the people of Demak in the 16th century. This study uses historical research methods because the data used are historical data about the function of wayang kulit as a medium for spreading Islam Demak 16th century. The historical method has four steps in conducting historical research: heuristics, criticism, interpretation and historiography. The results show that wayang kulit is a traditional art of Indonesian people that developed since the fifteenth century presented by a puppeteer by presenting classical stories such as plays in Ramayana and Mahabharata stories. The ancestors of the Indonesian people are animism and dynamism, who believe that every object has power and spirit, so that puppets are manifested into the form of statues and images. In which each form of wayang has the power symbolized on the shape of the size and the face of the puppets. The spread of the religion of Islam in Demak was done by Wali Songo through the existing artistic either modifying the story or creating a new puppet figure previously (in the Hindu period). Pandavas is a result of the acculturation of puppets, such as figures of punakawan which has a very deep philosophical meaning, because the puppet has an important role in Islamic preaching in demak. The function of wayang kulit in Demak society is as entertainment media, education, lighting, art, philosophy understanding, media of preaching and others. Function of wayang kulit is growing increasingly, wayang kulit is also used as a means to introduce Indonesia to the world as souvenirs, wall decorations or other home decor. Thus, wayang kulit many functions, not fixed and will continue to grow. Keywords: Function, Wayang Kulit, Spreading of Islam, Demak